TEMPORAL PARADOX IN THE FILM THE TIME TRAVELER'S WIFE (2009) - Widjaja, Frederik Agnar (Global Expert: Jurnal Bahasa dan Sastra, 2023)
This research paper aims to examine the temporal paradoxes portrayed in the film The Time Traveler's Wife (2009), a cinematic adaptation of the 2003 Audrey Niffenegger's novel of the same name. The film follows the story of Henry, an involuntary time traveler who, uncontrollably and unpredictably, travels through his life timeline. As he travels back and forward in time, Henry occasionally meets his wife, Clare, through her different stages of life, starting with her as a six-year-old child. The occasions in Henry's time-travelling life create some temporal paradoxes in both Henry's and Clare's life timelines. A temporal paradox occurs when there is an apparent or logical self-contradiction as a result of the idea of time travel, further classified into bootstrap paradoxes, grandfather (or consistency) paradoxes, and Newcomb's paradox. This study takes the data of lines from the film’s screenplay, written by Bruce Joel Rubin, that express or imply temporal paradoxes. The film touches upon all three types of paradoxes in different degrees. Bootstrap paradoxes include: (1) the meeting of Henry and Clare; (2) winning the lottery and buying the house; (3) the meeting of Henry and Dr Kendrick, a geneticist who helps Henry's Chrono-Impairment disorder condition; and (4) the naming of Alba, their only daughter. Each of the bootstrap paradoxes involves a causal loop–events whose causes are their own effects. The grandfather paradox deals with Henry’s inability to change the past despite being a time traveler who can travel back to the past. Newcomb’s paradox discusses all of the paradoxes and their relation to free will, especially Clare’s choice to marry Henry. By engaging with elements of time travel in a film, this paper offers a new insight into research on time travel narratives in literary works. Keywords: Temporal paradox, time travel, causal loops, bootstrap paradox, grandfather paradox, Newcomb’s paradox